2016
DOI: 10.4238/gmr.15027718
|View full text |Cite
|
Sign up to set email alerts
|

Association of single nucleotide polymorphisms in pro-inflammatory cytokine and toll-like receptor genes with pediatric hematogenous osteomyelitis

Abstract: ABSTRACT. Hematogenous osteomyelitis (H O ) is a bone infectionwherein bacteria penetrate to the bone through the blood stream. Several single nucleotide polymorphisms (SNPs) have been associated with susceptibility to infectious diseases. In this study, we investigated the contribution of SNPs in interleukin (IL)-1B1 (rs16944), IL1A (rs1800587), IL1B (rs1143634), toll-like receptor (TLR)-2 (rs3804099), TLR4 (rs4986790), TLR4 (rs4986791), IL1R (rs2234650), tumor necrosis factor (TNF)-α (rs1800629), TNF (rs3615… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…Activation of microglia and astrocytes with increased levels of pro-inflammatory serum and CSF cytokines IL-1β, IL-6, IL-8, TNF and vascular endothelial growth factor (VEGF) is considered the hallmark in ALS (Ciervo et al 2017;Hu et al 2017;Morello et al 2017;Crisafulli et al 2018). Interventions with corticosteroids and/or other anti-inflammatory drugs such as the COX-2 inhibitor celecoxib, which causes the reduction of the brain levels of inflammatory cytokines TNF and IL-1β (Osman et al 2016), however, were found ineffective in experimental ALS-like animals and/or ALS patients (Galbiati et al 2012;Collins and Bowser 2017;Crisafulli et al 2018). Apart from an eventual, subtle, inconsistent increase of survival time in ALS which might be seen in some patients after an intervention with riluzole (Miller et al 2012) and/or edaravone (Yoshino and Kimura 2006), disease-modifying interventions, for instance, adequate inflammasome-targeted strategies, are still an unmet need in most neurodegenerative disorders (Voet et al 2019).…”
Section: Anti-inflammatory Drug Interventions In Neurodegenerationmentioning
confidence: 99%
“…Activation of microglia and astrocytes with increased levels of pro-inflammatory serum and CSF cytokines IL-1β, IL-6, IL-8, TNF and vascular endothelial growth factor (VEGF) is considered the hallmark in ALS (Ciervo et al 2017;Hu et al 2017;Morello et al 2017;Crisafulli et al 2018). Interventions with corticosteroids and/or other anti-inflammatory drugs such as the COX-2 inhibitor celecoxib, which causes the reduction of the brain levels of inflammatory cytokines TNF and IL-1β (Osman et al 2016), however, were found ineffective in experimental ALS-like animals and/or ALS patients (Galbiati et al 2012;Collins and Bowser 2017;Crisafulli et al 2018). Apart from an eventual, subtle, inconsistent increase of survival time in ALS which might be seen in some patients after an intervention with riluzole (Miller et al 2012) and/or edaravone (Yoshino and Kimura 2006), disease-modifying interventions, for instance, adequate inflammasome-targeted strategies, are still an unmet need in most neurodegenerative disorders (Voet et al 2019).…”
Section: Anti-inflammatory Drug Interventions In Neurodegenerationmentioning
confidence: 99%
“…Previous reports have indicated that IL-1R1 genetic polymorphisms are associated with many inflammatory diseases, such as atopic asthma, alcoholic liver disease, hematogenous osteomyelitis, invasive pneumococcal disease, and IgA nephropathy [19][20][21][22][23]. A lot of research also have shown that non-coding single nucleotide polymorphisms (SNPs) have functional effects [24][25][26], even more, Saykin et al found that IL1RAP rs12053868, not a coding SNP, is associated with decreased IL1RAP expression in the cortex and hippocampus, thereby increasing amyloidosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have indicated that IL-1R1 genetic polymorphisms are associated with many inflammatory diseases, such as atopic asthma, alcoholic liver disease, hematogenous osteomyelitis, invasive pneumococcal disease, and IgA nephropathy [19][20][21][22][23]. A lot of researches also have shown that non-coding single nucleotide polymorphisms (SNPs) have functional effects [24][25][26], even more, Saykin et al found that IL1RAP rs12053868, not a coding SNP, is associated with decreased IL1RAP expression in the cortex and hippocampus, thereby increasing amyloidosis [14].…”
mentioning
confidence: 99%